2010
DOI: 10.1063/1.3524493
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic room temperature ferromagnetism in boron-doped ZnO

Abstract: We report room temperature ferromagnetism in boron-doped ZnO both experimentally and theoretically. The single phase Zn 1-x B x O films deposited under high oxygen pressure by pulsed-laser deposition show ferromagnetic behavior at room temperature. The saturation magnetization increases monotonously from 0 to 1.5 emu/cm 3 with the increasing of B componentx from 0 to 6.8%. The first-principles calculations based on density functional theory demonstrate that the ferromagnetism in B-doped ZnO originates from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Furthermore, doping can be used to effectively tune the width of the band gap of ZnO, which will in turn affect the optical properties of ZnO [16][17][18]. Among the various kinds of doped ZnO, B-doped ZnO (BZO) has recently been extensively investigated because of its utilitarian application as a transparent conductive oxide [19] and its ferromagnetic properties [20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, doping can be used to effectively tune the width of the band gap of ZnO, which will in turn affect the optical properties of ZnO [16][17][18]. Among the various kinds of doped ZnO, B-doped ZnO (BZO) has recently been extensively investigated because of its utilitarian application as a transparent conductive oxide [19] and its ferromagnetic properties [20].…”
Section: Introductionmentioning
confidence: 99%
“…In sharp contrast with this, Yi et al [15] reported that the p-type DMSs showed an enhanced magnetic moment when nitrogen was introduced to the C-doped ZnO films. Our earlier theoretical and experimental studies have shown that the nonmagnetic ion B-doped ZnO films have RTFM which appears to be related to the B dopants and the high growth oxygen partial pressure [16]. In this paper, we report our further investigation on the effect of carries type on the magnetic properties of B-doped ZnO films.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, FM has been observed in nonmagnetic element doped ZnO films, such as carbon, lithium or boron doped ZnO thin films. [23][24][25] Therefore, "d 0 -element" doping opens a new method to find ZnO DMS. As a tetravalent element, Si is considered to be a suitable d 0 dopant for inducing FM to ZnO system.…”
Section: Introductionmentioning
confidence: 99%